Pengaruh Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian Konsumen pada Restoran Aroma Kitchen Kota Padang - Fahimah Fitri Afifi; Arry Widodo (Ekonomis: Journal of Economics and Business, 2021)
This research is motivated by the increasingly rapid business growth in the city of Padang, especially in the culinary field. The development of restaurants that continues to increase makes business competition in the city of Padang quite competitive. With intense competition, culinary business people are required to think creatively in carrying out the right strategy to attract the attention of consumers. This study aims to determine and analyze the price and quality of service on consumer purchasing decisions at the Aroma Kitchen Restaurant in Padang City and their influence. The research method used in this research is quantitative with descriptive analysis and causality with the consumer population of Aroma Kitchen Restaurant. The sampling technique used is non-probability sampling with purposive sampling type and the number of respondents is 100 respondents. The data analysis technique used is descriptive analysis and multiple linear regression analysis. Based on the results of the descriptive analysis of the variables of price, service quality and purchasing decisions are in good category. The results of this study indicate that based on the variables measured simultaneously, namely price and service quality, it has a positive and significant effect on purchasing decisions. While the partially measured variables, namely price and service quality affect purchasing decisions.